2016
DOI: 10.1111/cmi.12687
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in innate immunity and autophagy during mycobacterial infection

Abstract: The fine-tuning of innate immune responses is an important aspect of host defenses against mycobacteria. MicroRNAs (miRNAs), small non-coding RNAs, play essential roles in regulating multiple biological pathways including innate host defenses against various infections. Accumulating evidence shows that many miRNAs regulate the complex interplay between mycobacterial survival strategies and host innate immune pathways. Recent studies have contributed to understanding the role of miRNAs, the levels of which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 85 publications
1
53
0
Order By: Relevance
“…It has been reported that several miRNAs are involved in the functions and development of host innate immune cells. For instance, the expression level of several miRNAs (e.g., miR‐21, miR‐9, miR‐146, miR‐147, and miR‐155) is upregulated during the infection‐induced inflammatory response of macrophage . The relationship between the NF‐κB signaling pathway and miR‐146a expression has been observed in some studies .…”
Section: Mir‐146amentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that several miRNAs are involved in the functions and development of host innate immune cells. For instance, the expression level of several miRNAs (e.g., miR‐21, miR‐9, miR‐146, miR‐147, and miR‐155) is upregulated during the infection‐induced inflammatory response of macrophage . The relationship between the NF‐κB signaling pathway and miR‐146a expression has been observed in some studies .…”
Section: Mir‐146amentioning
confidence: 96%
“…For instance, the expression level of several miRNAs (e.g., miR-21, miR-9, miR-146, miR-147, and miR-155) is upregulated during the infection-induced inflammatory response of macrophage. 14 The relationship between the NF-κB signaling pathway and miR-146a expression has been observed in some studies. 3 In an investigation, Taganov et al 12 found that miR-146a expression was induced upon the stimulation with lipopolysaccharides in an NF-κB-dependent manner, and miR-146a targeted the IRAK1 and TRAF6 genes.…”
Section: Mir-146amentioning
confidence: 97%
“…For a robust selection of DMG-miRNAs, we further narrowed down the list to only include those miRNAs that target at least two DMGs, leaving a total of 129 unique DMG-interacting miRNAs for further analysis. In parallel to this, we also prepared a list of 313 miRNAs that have been linked to mycobacterial exposure of human cells or tissues in previously published literature [24,25]. Matching the DMG-miRNA with these mycobacteria-specific miRNAs, we found that 24 of the 129 DMG-miRNA were represented in the list of miRNAs related to mycobacterial exposure.…”
Section: Justification Of the Bcg Responder Module By Validation Agaimentioning
confidence: 99%
“…While the role of miRNAs in bacterial infections has been extensively studied and excellently reviewed in previous years (Eulalio et al, 2012; Das et al, 2016; Kim et al, 2017), we are beginning to realize the pivotal role of another class of regulatory RNA molecules, which are collectively referred to as long non-coding RNAs (lncRNAs). Next-Generation RNA sequencing (RNAseq) studies have examined that the majority of the mammalian genome is transcribed but very little of it has the ability to encode for proteins (Birney et al, 2007).…”
Section: Introductionmentioning
confidence: 99%